2020
DOI: 10.1101/2020.10.02.323840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variations in the frequency and amplitude of resting-state EEG and fMRI signals in normal adults: The effects of age and sex

Abstract: Frequency and amplitude features of both resting-state electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) are crucial metrics that reveal patterns of brain health in aging. However, the association between these two modalities is still unclear. In this study, we examined the peak frequency and standard deviation of both modalities in a dataset comprising healthy young (35.5±3.4 years, N=134) and healthy old (66.9±4.8 years, N=51) adults. Both age and sex effects were examined using n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…These brain changes were further hypothesized to be related with disrupted network-level flexibility, for example, the inability to coherently decrease and increase brain region activity when engaging in mathematical tasks (Jolles et al, 2016). Prior multimodal studies performed on adults have shown that fMRI and EEG signal amplitudes are modulated by effects of aging and sex (Zhong & Chen, 2020), with the hypothesis that as vasculature reactivity declines with age, so does BOLD-signal amplitude (Zhong & Chen, 2020). Contrarily, frequency bands of MEG-fMRI measurements follow similar power-law distributions with electrophysiological signals, suggesting that intensity of low-frequency modulations stem from neural activity rather than neurovascular coupling effects (Zhang et al, 2022).…”
Section: The Possible Underpinnings Of Falff and Rehomentioning
confidence: 99%
“…These brain changes were further hypothesized to be related with disrupted network-level flexibility, for example, the inability to coherently decrease and increase brain region activity when engaging in mathematical tasks (Jolles et al, 2016). Prior multimodal studies performed on adults have shown that fMRI and EEG signal amplitudes are modulated by effects of aging and sex (Zhong & Chen, 2020), with the hypothesis that as vasculature reactivity declines with age, so does BOLD-signal amplitude (Zhong & Chen, 2020). Contrarily, frequency bands of MEG-fMRI measurements follow similar power-law distributions with electrophysiological signals, suggesting that intensity of low-frequency modulations stem from neural activity rather than neurovascular coupling effects (Zhang et al, 2022).…”
Section: The Possible Underpinnings Of Falff and Rehomentioning
confidence: 99%
“…This limitation may have directly influenced the iEEG results. Furthermore, previous work suggests a potential age effect on band power profiles in children 59 , 60 and in elderly 61 , 62 , which was not investigated in our study of adult participants. We also used a single template MRI (ICMB152) to build realistic head models that limits the anatomical precision of source localisation.…”
Section: Discussionmentioning
confidence: 71%
“…Corresponding to the age-related differences in temporal neural dynamics, resting-state spectral power also shows significant differences in frequency band power between younger and older individuals 97 . Even though there are inconsistencies in the current literature, in general, low frequencies (delta, theta, alpha bands) show decreased power 91,[98][99][100] , while higher frequencies (beta) show increased power 92,101 with healthy aging (i.e., and age-related shift in spectral power density; [102][103][104][105][106][107] ). These results are in line with the age-related brain signal complexity changes, namely the decreased power in lower frequency bands with healthy aging can be linked to decreased coarse time scale entropy while the increased power in higher frequency bands can be linked to increased fine time scale entropy 88 .…”
mentioning
confidence: 93%